Aggravation of cases of Sexual Violence against Children and Adolescents during the COVID-19 Pandemic in Brazil: A systematic review of literature (Research, Society and Development, 2022)
Sexual violence against children and adolescents (SVACA) is an epidemic, which continues to have numerous consequences for individual and collective health. Due to the worsening of the pandemic, triggered by the SARS-CoV-2 virus, and the fundamentality of the determination of restrictive measures that began in March 2020, an increase in the vulnerability of the victims was evidenced, who remained distant from agents of their main support network, the schools. Objective: To analyze the aggravation of cases of SVACA during the COVID-19 pandemic in Brazil. Methodology: Systematic review of qualitative and exploratory character, following the PRISMA protocol. Results: They showed that among the victims aged 0 to 9 years, girls represent 77%, while between 10 and 19 years old, the female sex corresponds to 91% of the records, in other words, 86.9% of the victims of child sexual abuse are girls. As for the perpetrators, 85.2% were known to the victims and 96.3% were male – relatives, close people with free access to children, which make the complaint process even more difficult. Conclusion: The increase in cases is evident in Brazil, especially in female children and adolescents, and that social isolation limited the possibility for victims to seek support networks. It should be noted that the identification of vulnerable groups and their protection only occurs through their notification and the development of public policies in all spheres – health, social assistance, education, public security, etc. – and, of course, civil society.